Kompetensi Sosial Anak di Era Digital dilihat dari Berbagai Suku Budaya - Dewi Sri Mustikasari; Esti Widya Rahayu (Universitas Muhammadiyah Malang, 2023)
Every person in various regions has different values of social and emotional aspects in life. Background Children’s culture has an important role in contributing to these differences in values. Attitudes and behavior of children throughout their life span and development are also determined by the culture in which they grow up. These cultural values can see in the various tribes in Indonesia, including the Javanese (andhap ansor ), Bugis-Makassar (siri) and Papua (the tendency is more on emotional expression). This study aims to see differences in social abilities of the Javanese, Bugis-Makassar, and Papuan tribes in the social-emotional aspects of children that focus on social awareness, responsible decision-making, and relationship skills. The results of the data analysis show that there are different aspects socio-emotional competence of children in the Javanese, Bugis-Makassar, and Papuan ethnic groups.